2004
DOI: 10.1242/dev.01205
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genetic interactions betweenSTYLOSAandGRAMINIFOLIAin the control ofAntirrhinumvegetative and reproductive development

Abstract: GRAMINIFOLIA (GRAM), is supported by enhanced phenotypic defects in sty gram double mutants, for instance in the control of phyllotaxis, floral homeotic functions and organ polarity. Accordingly, the STY and GRAM protein and mRNA expression patterns overlap in emerging lateral organ primordia. STY is expressed in all meristems and later becomes confined to the adaxial domain and (pro)-vascular tissue. This pattern is similar to genes that promote adaxial identity, and, indeed, STY expression follows, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 57 publications
2
93
1
4
Order By: Relevance
“…One molecular explanation for a differential requirement for SEU and LUG is that they may have multiple protein partners and may participate in a number of different complexes that are required for diverse developmental events. A family of SEUSS-LIKE (SLK) genes has been described in Arabidopsis (Franks et al, 2002), and Antirrhinum members of this family have been shown to physically interact with STYLOSA, the Antirrhinum LEU ortholog (Navarro et al, 2004). Thus, the SLK gene family may support SEU-independent activities of LUG in the seu mutant plants.…”
Section: Differential Contributions Of Seu and Lug To Gynoecial And Fmentioning
confidence: 99%
See 2 more Smart Citations
“…One molecular explanation for a differential requirement for SEU and LUG is that they may have multiple protein partners and may participate in a number of different complexes that are required for diverse developmental events. A family of SEUSS-LIKE (SLK) genes has been described in Arabidopsis (Franks et al, 2002), and Antirrhinum members of this family have been shown to physically interact with STYLOSA, the Antirrhinum LEU ortholog (Navarro et al, 2004). Thus, the SLK gene family may support SEU-independent activities of LUG in the seu mutant plants.…”
Section: Differential Contributions Of Seu and Lug To Gynoecial And Fmentioning
confidence: 99%
“…These phenotypes are not observed in the seu ant double mutants (data not shown), highlighting a degree of functional differentiation between SEU and YAB1/ FIL. Evidence that SEU and LUG may physically cooperate with YAB1/FIL comes from the analysis of orthologous genes in Antirrhinum majus (Navarro et al, 2004). STYLOSA (STY), the Antirrhinum ortholog of LUG, has been shown to interact physically with members of the Antirrhinum YABBY and SLK gene families suggesting that the orthologous Arabidopsis proteins (SEU, YAB1/FIL, CRC, and LUG) may be part of a multimeric complex important for the development of the medial domain of the gynoecium.…”
Section: Yabby Gene Familymentioning
confidence: 99%
See 1 more Smart Citation
“…lug mutants showed defects in gynoecium development, female and male fertility, leaf and floral organ shape, and vasculature (Liu and Meyerowitz, 1995;Chen et al, 2000;Liu et al, 2000;Cnops et al, 2004;Franks et al, 2006). Antirrhinum mutants of STYLOSA, a LUG ortholog, not only showed abnormal flower development but also exhibited hypersensitivity toward auxin and polar auxin inhibitors (Navarro et al, 2004). A transcriptome study identified LUG-regulated genes in abiotic and biotic stress response, meristem function, and transport (Gonzalez et al, 2007).…”
mentioning
confidence: 99%
“…Several transcription factors participate in this control, which aims at transcriptional silencing of the so-called 'C genes' outside their genuine expression domain in the inner two whorls of the flower, where they govern reproductive organ (stamen and carpel) development 6,7 . The functions of orthologous repressor genes, constituting the A function of the floral ABCs 6 , are, in part, comparable between different species 8 , as are some of the cis-acting regulatory regions within the large second intron of their structurally and functionally related target C genes AGAMOUS (AG) in Arabidopsis thaliana 7 , pMADS3 in P. hybrida 9 and PLENA and FARINELLI (PLE and FAR) in A. majus 10 . There are also exceptions to these overall similarities among species.…”
mentioning
confidence: 99%